Representações de hispanofalantes latino-americanos sobre a aprendizagem de português e a preparação para o Celpe-Bras - Marina de Paulo Nascimento (2020)
This investigation integrates the researches context of Portuguese as an Additional Language for Spanish speakers and focuses on the representations of three Spanish speakers and Latin American people on the processes of learning the Brazilian Portuguese Language and the preparation process for proficiency assessment in this idiom. The motivation for this study is based on the need to get know the ways in which people with these characteristics represent the processes of learning Brazilian Portuguese and preparing for Celpe-Bras, given the linguistic proximity between Spanish and Portuguese, as well as the responsible nuances by the displacement of countless individuals towards the country and referenced exam. In this perspective, among the theoretical assumptions guiding this work are the studies of Representations (DURKHEIM, 1974; LEFEBVRE, 1983; MOSCOVICI, 2000; CHARTIER 2002) and Learning Strategies (RUBIN, 1975; OXFORD, 1990; 2017), of Intercomprehension (DEGACHE E GARBARINO, 2017; DE PAULO, 2017; ERAZO 2016) and Portuguese As an Additional Language Teaching-Learning for Spanish speakers (ALMEIDA-FILHO, 1995; RABASA, 2010; GRANNIER E CARVALHO, 2015; ROBLES E ROCHA, 2017). The investigative hypothesis of the current construct is that the dynamic representations about learning and preparation under study are also related to the socioeconomic motivations (GARDNER, 1985) of the individuals addressed. Considering so, the main objective of this research is to highlight the representations of three Latin American Spanish speakers in terms of learning Brazilian Portuguese and preparing for the assessment indicated. To achieve the proposed goals, we developed a Preparatory Course for the Celpe-Bras Examination before and after which, individually, those involved participated of a 1) Semi-structured interview about their PLA learning processes and preparation for Celpe -Bras. During the interviews and preparatory classes, (2) Field notes on these same issues were elaborated. The records generated from these instruments were organized with a view to a qualitative analysis (Richards, 2003) based on the construction of categories and subcategories of subsidies according to the similarities between their meanings (Flick, 2018). In such a way, on the one hand, these records demonstrate a representation on the part of the subjects involved in Learning Portuguese effort, as well as contact with native Portuguese speakers. On the other hand, that Preparation for Celpe-Bras presents itself as an indispensable condition to achieve certification in this proficiency assessment, as dependent on the partnership, especially with Brazilian Portuguese speakers as their mother tongue.